Influence of Dammar Resin on the Mechanical Properties of Composites Reinforced with Corn Husk and Paper Waste - Cosmin Mihai Miritoiu (BioResources)
This study aimed to investigate the influence of dammar resin on the mechanical properties of composite materials reinforced with corn husk and paper waste laminates. Different percentages of dammar resin (50%, 60%, and 70%) were added to the matrix while keeping the reinforcement constant. For all samples, the ratio was maintained at 40% matrix and 60% reinforcement. With the experimental results obtained, statistical analyses were conducted: two-way analysis of variance (ANOVA), Levene's test, Shapiro-Wilk test, and ANOVA post hoc (with Bonferroni correction). The null hypothesis stated that dammar resin does not influence the mechanical properties. For all tests considered, the null hypothesis was rejected (p < 0.05), the variances were homogeneous (p > 0.05), and the data followed a normal distribution (p > 0.05). It was found that dammar resin had a significant influence on the mechanical properties as the percentage increased from 50% to 70% (p < 0.0083). For each test, based on already known premises, an explanation of the phenomenon that could occur due to the insertion of dammar resin was provided, serving to complement and validate the statistical estimations.